Students' experiences with different learning pathways to higher professional bachelor programmes - Harm J.A. Biemans; Hans Mariën; Erik Fleur; Tanya Beliaeva; Jan Harbers (European Research Network Vocational Education and Training (VETNET), 2020)
Context: In the Dutch educational system, different learning pathways to higher professional bachelor (or HBO) programmes have been created: the regular VET route, the general secondary education route, and continuing learning pathways (such as the Green Lyceum or GL) that combine characteristics of these two traditional routes and that are specifically designed for students who combine a relatively high cognitive level with an affinity for practical, vocation-oriented assignments.  Approach: The present study aimed to compare the experiences of students coming from these three different learning pathways to HBO. 62 former GL students, 127 former middle-management VET (or MBO) students, and 81 former regular general secondary education (or HAVO) students completed an online questionnaire on their experiences in their first HBO study year and their scores on the various scales were compared.  Findings: Students from the three groups were equally satisfied with their current HBO programme. The same pattern was found for perceived study success in their HBO programme. Former GL students, however, mentioned that they had been better prepared in terms of development of study skills needed in HBO. Compared with the MBO route to HBO, former GL students felt better prepared in terms of the theoretical subjects addressed in their previous educational programme. In this regard, their level of theoretical preparation was comparable to that of former HAVO students. When the vocation-oriented aspects of education were concerned, however, the GL appeared to be comparable with the MBO route to HBO (in the HAVO curriculum, vocation-oriented preparation for HBO is absent). Moreover, former HAVO students scored lower than former GL and former MBO students with respect to the extent to which they felt that they had received support in choosing a particular HBO programme in their previous educational programme. Conclusion: The GL seems to combine the advantages of MBO and HAVO programmes for this particular group of students: theoretical preparation for HBO at HAVO level combined with practical preparation at MBO level, systematic career orientation and guidance, and development of study skills required in HBO. In other words, such continuing learning pathways can be a curriculum design solution for specific student groups to promote their transition to HBO.